The Lattice Compatibility Theory: Supports from the Generalized Simha-Somcynsky Chemical Physics-Related Theory. (5th August 2013) - Boubaker, K.; Colantoni, A.; Petkova, P.
Abstract : The earliest models used in the study of lattice structures are mean field theories, which do not contain structural dependence. The Lattice Compatibility Theory (LCT) proposes here a novel framework where the measure of the disorder is based on Urbach tailing features and lattice matching features between the host matrix and doping agent intrinsic structures. This study has been implemented on a particular compound (BTO:Co) and refers to the Simha-Somcynsky (SS) theory, a mean field theory where the measure of the disorder is stated as holes.